Beyond the “Conflict” Paradigm - Aziz Douai (International Institute of Islamic Thought, 2016)
Western-Muslim relations have experienced long periods of peaceful coexistence, fruitful co-operation, and close interactions that have enriched both civilizations. And yet an alien observer of our mainstream media could be forgiven for concluding that “Islam” and the “West” can never co-exist in peace because they seem to have nothing in common. In fact, the intermittent violence interrupting these long peaceful interactions – from the Crusades to the “War on Terror” – has constituted the core of most mainstream media coverage and “scholarship” purporting to “study” and “explain” these relations. In a zero-sum power game, these dominant frameworks emphasize that such a “clash” is inevitable. Samuel Huntington’s “Clash of Civilizations” theory has become the best known articulation and deployment of “conflict” as an “explanatory” framework for understanding current and past Muslim- West interactions. Simply put, existential, cultural, and religious chasms have put the Muslim world on a collision course with the western world, a problem that is most exacerbated by the presence of “Islam” and Muslim communities in western societies (Huntington, 1993).1 His thesis appears to ignore each civilization’s internal diversity and pluralism and to be willfully oblivious to the inter- and intra-civilizational interactions and centuriesold co-existence, as Edward Said argued in his rebuttal: “Clash of Ignorance” (2001).